Vancomycin-sensitive E. faecalis transferred to resistant isolates after multiple mixed subcultures with vancomycin-resistant S. aureus isolated Women with Genital Tract Infection - Arif, Asraa Ali; Hamada, Prof. Dr. Thekra Ahmed; Hasni, Ibtissem (South Eastern European Journal of Public Health, 2024)
Background: Vaginitis, characterized by inflammation of the vagina, is a prevalent health issue affecting millions of women worldwide which is often attributed to an imbalance in vaginal microbiota and is the most common cause of vaginal discharge in reproductive-aged women. Aim: The aim of this study is to investigate the molecular transferring of vancomycin-sensitive Enterococcus faecalis to resistance isolates following multiple mixed subcultures with vancomycin-resistant Staphylococcus aureus in women with genital tract infection. Materials and methods: A cross-sectional study conducted in Tikrit City, Balad Province, from February 2023 to March 2024 involved 400 married, non-pregnant women aged 15-49 with vaginitis symptoms. These women sought consultation at Balad General Hospital's clinic and private clinics in the province. The study received approval from the council of the College of Medicine, Tikrit University. Bacterial isolation from vaginal samples was performed by gently inserting a swab into the vaginal opening, rotating it against the vaginal walls, and then carefully withdrawing it without touching the skin. The collected swabs were cultured on various selective media, including blood agar, MacConkey agar, Sabouraud's dextrose agar, azide blood agar, chromogenic agar (UTIC), and CHROM agar candida. Real- Interpretation of RT-PCR data relied on Ct values, which indicate the cycle number at which the fluorescence signal surpasses the baseline threshold. Higher Ct values correspond to lower gene expression or amplification, while lower Ct values indicate higher gene expression or amplification. The accuracy of gene amplification was assessed by the Ct values obtained from triplicate reactions.